FPGA Implementation of Uniform Random Number based on Residue Method - Z Zulfikar (Universitas Syiah Kuala, 2014)
This paper presents the implementation and comparisons of uniform random number on Field Programable Gate Array (FPGA). Uniform random numbers are generated based on residue method. The circuit of generating uniform random number is presented in general view. The circuit is constructed from a multiplexer, a multiplier, buffers and some basic gates. FPGA implementation of the designed circuit has been done into various Xilinx chips. Simulation results are viewed clearly in the paper. Random numbers are generated based on different parameters. Comparisons upon occupied area and maximum frequency from different Xilinx chip are examined. Virtex 7 is the fastest chip and Virtex 4 is the best choice in terms of occupied area. Finally, Uniform random numbers have been generated successfully on FPGA using residue method.Keywords: FPGA implementation, random number, uniform random number, residue method, Xilinx chips